2013
DOI: 10.1097/nen.0b013e31827bced3
|View full text |Cite
|
Sign up to set email alerts
|

Diffusely Abnormal White Matter in Multiple Sclerosis: Further Histologic Studies Provide Evidence for a Primary Lipid Abnormality With Neurodegeneration

Abstract: Although multiple sclerosis (MS) lesions have been studied extensively using histology and magnetic resonance imaging (MRI), little is known about diffusely abnormal white matter (DAWM). Diffusely abnormal white matter, regions with reduced mild MRI hyperintensity and ill-defined boundaries, show reduced myelin water fraction, and decreased Luxol fast blue staining of myelin phospholipids, with relative preservation of myelin basic protein and 2',3'-cyclic-nucleotide 3'-phosphohydrolase. Because DAWM may be im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 78 publications
8
85
0
Order By: Relevance
“…We found decreases in sphingomyelin and sulfatides in myelin lipids isolated from NAWM in MS samples compared to controls. These observations are supported by other studies which have analyzed postmortem white matter in MS and reported lipid abnormalities and changes in lipid content including sphingolipids and sulfatides (Alling et al 1971; Marbois et al 2000; Laule et al 2013). The fact that these decreased sphingomyelin levels were correlated with NAA levels suggested that defects in neuronal metabolism in MS and reduced NAA may be involved in changes to myelin lipid composition.…”
Section: Discussionsupporting
confidence: 87%
“…We found decreases in sphingomyelin and sulfatides in myelin lipids isolated from NAWM in MS samples compared to controls. These observations are supported by other studies which have analyzed postmortem white matter in MS and reported lipid abnormalities and changes in lipid content including sphingolipids and sulfatides (Alling et al 1971; Marbois et al 2000; Laule et al 2013). The fact that these decreased sphingomyelin levels were correlated with NAA levels suggested that defects in neuronal metabolism in MS and reduced NAA may be involved in changes to myelin lipid composition.…”
Section: Discussionsupporting
confidence: 87%
“…In particular, Kutzelnigg et al (4) summarized the pathologic features of DAWM in progressive MS as follows: general sparing of subcortical U-fibers, loss of myelin staining as a result of decreased fiber density (axons and myelin) with apparent absence of primary demyelination, and frequent presence of axonal swelling. In contrast, Laule et al (6) found that myelin pathology in DAWM is more prominent and most likely resulted in the intermediate axonal degeneration. Numerous spheroids in normally myelinated areas were also described in the quantitative study by Trapp et al (5), who studied 47 demyelinating lesions in 11 MS patients.…”
Section: Discussionmentioning
confidence: 88%
“…However, in regression analysis, we found that only the relatives of subjects with MS who showed WM signal abnormalities or had Ն9 WM signal abnormalities and fulfilled RIS-Swanton criteria had elevated smoking and obesity vascular risk factors. It could be hypothesized that these risk factors may play a different role in formation of WM signal abnormalities in individuals genetically susceptible for MS, as are relatives of patients with MS. A recent study suggested that primary lipid abnormality in DAWM may be involved in demyelination and axonal degeneration of patients with MS, 38 and obesity was recently suggested as linked with increased morbidity for MS. 27 Persons with RIS are at an increased risk of development of MS. 39,40 During a follow-up period of 2-5 years, approximately one-third of patients had clinical symptoms characteristic of MS. 39,40 Increased risk for clinical conversion was observed in younger subjects, with a higher number of lesions, presence of infratentorial lesions, pathologic evoked potentials, positive oligoclonal bands, and spinal cord lesions. 40 The limitation of our study was that it was a cross-sectional pilot study that did not include spinal cord MR imaging, and no information is currently available about longitudinal follow-up of the enrolled subjects.…”
Section: Discussionmentioning
confidence: 99%